Urban Green Open Space in Metro, Lampung, Indonesia: Vegetation Structure, History, and Function - Wakhidah, Anisatu Z.; Anggraini, Ervita; Hanifah, Muti; Nurlillah, Revi; mulyani, Selly (Media Konservasi, 2024)
Urban areas with high population density and air pollution need a green open space (GOS). GOS is an open land with plant vegetation as a constituent needed to support ecological functions and improve environmental quality in urban areas. Metro city has a number of GOS that haven’t been reported about its plant structure and composition. The purpose of this study was to determine the GOS’ composition of plants and structure in Metro City; describe the history of each GOS; its social and ecological function. The research was conducted at a number of GOS in Metro city with quantitative and survey methods. Data collected by direct observation and exploring each location point. This study observed two types of GOS which have different structures in Metro City, namely ground and parks. The results showed that before the area became GOS, it was vacant land as government property. Furthermore, recorded as many as 1,198 individual plants identified as 112 species belonging to 43 families plant composed the vegetation in GOS’ area. Fabaceae was the most occurred family, while Acacia auriculiformis A. Cunn ex Benth and Imperata cylindrical (L.) were dominant species in the observed GOS. The diversity index (H’) in all observed GOS were medium category, the highest evenness index (J) is found in GDR (0.92) while the lowest is in KHD (0.57). Generally, GOS in Metro city utilized as research filed, recreation, economy activity, medium of social interaction, and functions ecologically as a buffer for the urban ecosystem.